Sindrom Stockholm Tokoh Cerita Dalam Roman Anak Perawan Di Sarang Penyamun: Analisis Psikologi Sastra - Akhsan, Taufik; Sudewa, I Ketut; Mas Triadnyani, I G.A.A. (Humanis, 2016)
The main presumption that used as basis of this research was the stockholm syndrome on Sayu. Concerning stockholm syndrome was a psychological phenomenon, therefore this research used two theories, which is structural theory and psychology litterature theory. The result of this reasearch concluded that Sayu’s behavior shows the individual dan situational characteristics of stockholm syndrome. The existence of stockholm syndrome in this work extraordinarily harmonize the entire plot element of Anak Perawan di Sarang Penyamun as one solid litterature work.